MODELLING OF INFLUENCE OF PARAMETERS OF THE BUNKER AND TRANSPORT WINDOWS ON PRODUCTIVITY OF THE BUNKER OF SEEDERS - S. B. Demin; D. V. Sinenkov (Вестник Дагестанского государственного технического университета: Технические науки)
In the article the influence of parameters of the bunker and transport boxes on the performance of the hopper units are plated. Recommendations on the choice of the main parameters for a given rate of sowing the seed culture.